VEGF Expression in Umbilical Cord MSC Depends on the Patient’s Health, the Week of Pregnancy in Which the Delivery Took Place, and the Body Weight of the Newborn – Preliminary Report - Bieńko K; Leszcz M; Więckowska M; Białek J; Petniak A; Szymanowski R; Wilińska A; Piszcz B; Krzyżanowski A; Kwaśniewska A; Płachno BJ; Gil-Kulik P; et al. (Stem Cells and Cloning: Advances and Applications, 2023)
Karolina Bieńko,1 Monika Leszcz,1 Marta Więckowska,1 Justyna Białek,1 Alicja Petniak,2 Rafał Szymanowski,2 Agnieszka Wilińska,2 Bartosz Piszcz,3,4 Arkadiusz Krzyżanowski,3 Anna Kwaśniewska,3 Bartosz J Płachno,5 Paulina Gil-Kulik,2 Janusz Kocki2 1Student Scientific Society of Clinical Genetics, Medical University of Lublin, Lublin, Poland; 2Department of Clinical Genetics, Medical University of Lublin, Lublin, Poland; 3Department of Obstetrics and Pathology of Pregnancy, Medical University of Lublin, Lublin, Poland; 4Doctoral School, Medical University of Lublin, Lublin, Poland; 5Department of Plant Cytology and Embryology, Institute of Botany, Faculty of Biology, Jagiellonian University, Kraków, PolandCorrespondence: Paulina Gil-Kulik, Department of Clinical Genetics, Medical University of Lublin, 11 Radziwillowska Str., Lublin, 20-080, Poland, Email paulina.gil-kulik@umlub.plIntroduction: Cells collected from Wharton’s jelly are a rich source of mesenchymal stem cells. They can be easily obtained and grown using the adhesive method. They produce many types of proteins, including VEGF. Their role is to participate in angiogenesis, vasodilation, stimulation of cells to migrate, and chemotactic activity. The aim of this study was to evaluate expression of genes from the vascular endothelial growth factor family: VEGFA, VEGFB and VEGFC in MSC and the analysis of dependence of the expression of the studied genes on clinical factors related to the course of pregnancy and childbirth, and health of mother and child.Material and Methods: The research material was an umbilical cord obtained from 40 patients hospitalized in the Department of Obstetrics and Pathology of Pregnancy of the Independent Public Clinical Hospital No.1 in Lublin. The age of the women was 21– 46, all gave birth by cesarean section. Some of the patients suffered from hypertension and hypothyroidism. Material collected from patients immediately after delivery was subjected to enzymatic digestion with type I collagenase. The isolated cells were then cultured in adherent conditions, and then gene expression was assessed using qPCR and the immunophenotype of the cells was assessed cytometrically.Results: Conducted studies have shown significant differences in expression of VEGF family genes depending on clinical condition of mother and child. Significant differences in VEGF-family gene expression level in umbilical cord MSC collected from women with hypothyroidism, hypertension, time of labor and birth weight of the baby were shown.Conclusion: Probably due to hypoxia (caused, for example, by hypothyroidism or hypertension), the MSCs found in the umbilical cord may react with an increased expression of VEGF and a compensatory increase in the amount of secreted factor, the aim of which is, i.a., vasodilation and increase of blood supply to the fetus through the umbilical vessels.Keywords: VEGF, mesenchymal stem cells, Wharton’s jelly, angiogenesis